Composite hydrogen-sensitive material as well as preparation method and application thereof
By combining palladium nanoparticles with porous material ZIF-8 to form a composite hydrogen-sensitive material, the problem of slow response speed of single palladium metal or nano-scale Pd-based hydrogen-sensitive material is solved, and rapid and high-sensitivity hydrogen detection is achieved at room temperature.
Patent Information
- Application Number
- CN202311165195.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, single palladium metal or nanoscale Pd-based hydrogen-sensitive materials have slow response speed at room temperature, making it difficult to meet the needs of high sensitivity and rapid detection of hydrogen.
By compounding palladium nanoparticles with the porous material ZIF-8, a composite hydrogen-sensitive material is formed. The palladium nanoparticles are evenly dispersed in the pores of ZIF-8, improving the selectivity, response speed and sensitivity of hydrogen.
It realizes rapid, high sensitivity and high selectivity detection of hydrogen under room temperature conditions, and can quickly respond to the leakage of hydrogen in the environment and ensure its safe use.
Smart Images

Figure CN119588926A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen-sensitive materials, and in particular to a composite hydrogen-sensitive material and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has the advantages of wide distribution, clean and renewable, high energy density and wide application. It is an emerging zero-carbon energy and is also considered to be an ideal energy source to replace fossil fuels. However, hydrogen is a colorless and odorless flammable gas with low ignition energy. It is very easy to explode when exposed to open flames or electric current. There are great safety hazards in hydrogen energy storage systems, vehicles, electrical appliances and the entire infrastructure involving hydrogen. Once there is a leak, it must be discovered early.
[0003] The hydrogen-sensitive material of existing hydrogen sensors is palladium (Pd). At room temperature, palladium can react reversibly with H2 to catalyze the dissociation of hydrogen into hydrogen atoms, thereby forming palladium hydride (PdHx) with a higher resistivity than Pd. Quantitative detection of H2 is achieved by detecting the resistance signal of the hydrogen sensor based on Pd-based hydrogen-sensitive materials. However, poor hydrogen sensing response and slow reaction kinetics are often observed with single palladium metal, and even the response speed of hydrogen sensors based on nanoscale Pd-based hydrogen-sensitive materials is still insufficient. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of slow response speed of single palladium metal or nano-scale Pd-based hydrogen-sensitive materials at room temperature in the prior art, and to provide a composite hydrogen-sensitive material and a preparation method and application thereof.
[0005] In order to achieve the above objectives, the present invention provides a composite hydrogen-sensitive material on one hand, wherein the composite hydrogen-sensitive material comprises a porous material ZIF-8 and palladium nanoparticles loaded on the porous material ZIF-8.
[0006] Preferably, in the composite hydrogen-sensitive material, the particle size of the palladium nanoparticles is in the range of 10 to 20 nm, and the morphology thereof includes one or more of a cube, an octahedron, a cuboctahedron and a sphere.
[0007] Preferably, the palladium nanoparticles are loaded in the pores of the porous material ZIF-8.
[0008] Preferably, the particle size of the composite hydrogen-sensitive material is in the range of 300 to 500 nm, and its morphology includes one or more of a cube, a rhombic dodecahedron and a sheet.
[0009] A second aspect of the present invention provides a method for preparing a composite hydrogen-sensitive material, the method comprising the following steps:
[0010] (1) mixing a palladium precursor, HCl and water, and mixing the obtained precursor solution with a surfactant and a reducing agent to react to obtain palladium nanoparticles;
[0011] (2) The palladium nanoparticles, 2-methylimidazole, a zinc source and a solvent are mixed and reacted.
[0012] Preferably, in step (1), the molar ratio of the palladium precursor to HCl in the precursor solution is 1:1-5.
[0013] Preferably, in the precursor solution, the concentration of the palladium precursor is 0.001-0.02 mol / L.
[0014] Preferably, in step (1), the palladium precursor is selected from one or more of palladium acetylacetonate, palladium chloride, palladium nitrate and palladium sulfate.
[0015] Preferably, in step (1), the surfactant is selected from one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, polyvinylpyrrolidone, cetylpyridinium chloride and sodium dodecylbenzene sulfonate.
[0016] Preferably, in step (1), the reducing agent is selected from one or more of ascorbic acid, sodium borohydride and sodium hypophosphite.
[0017] Preferably, in step (1), the molar ratio of the palladium precursor, the surfactant and the reducing agent is 1:4-20:0.4-2.
[0018] Preferably, in step (1), the reaction temperature is 50-100° C. and the reaction time is 1-13 h.
[0019] Preferably, in step (1), the step of mixing and reacting the obtained precursor solution with a surfactant and a reducing agent to obtain palladium nanoparticles comprises:
[0020] The obtained precursor solution and the surfactant are continuously mixed at 50-100° C., and then a reducing agent is added and reacted for 5-15 minutes, and then reacted at 50-100° C. for 1-12 hours;
[0021] The obtained reaction product is washed and dried at 40 to 100° C. for 12 to 36 hours to obtain palladium nanoparticles.
[0022] Preferably, the molar ratio of the palladium precursor to 2-methylimidazole is 1:10-60.
[0023] Preferably, in step (2), the molar ratio of the 2-methylimidazole to the zinc source is 1 to 4:1.
[0024] Preferably, in step (2), the reaction temperature is 0 to 50° C. and the reaction time is 1 to 8 h.
[0025] Preferably, in step (2), the zinc source is selected from one or more of zinc nitrate hexahydrate, zinc chloride and zinc sulfate;
[0026] Preferably, in step (2), the solvent is selected from one or more of methanol, N,N-dimethylformamide, ethanol, water and n-heptane.
[0027] Preferably, step (2) comprises:
[0028] A1, 2-methylimidazole, a zinc source and a solvent are mixed and stirred to obtain a mixed solution;
[0029] A2. Mixing the palladium nanoparticles with the mixed solution, stirring for reaction, and then washing, centrifuging and drying.
[0030] The third aspect of the present invention provides a composite hydrogen-sensitive material prepared by the method as described above.
[0031] A fourth aspect of the present invention provides a hydrogen sensor, wherein the raw materials for preparing the hydrogen sensor include the composite hydrogen-sensitive material as described above.
[0032] A fifth aspect of the present invention provides an application of the composite hydrogen-sensitive material as described above in hydrogen detection.
[0033] In the present invention, palladium nanoparticles and porous material ZIF-8 are compounded to improve the selectivity, response speed and sensitivity of palladium nanoparticles to hydrogen. The composite hydrogen-sensitive material provided by the present invention has good stability, can detect hydrogen quickly, highly sensitively and highly selectively at room temperature, and can be used for leakage and detection of hydrogen in an environment at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a TEM image of palladium nanoparticles prepared in Example 1 of the present invention;
[0035] Figure 2 is a TEM image of the composite hydrogen-sensitive material prepared in Example 1 of the present invention;
[0036] Figure 3 is a TEM image of palladium nanoparticles prepared in Example 4 of the present invention;
[0037] Figure 4 is a TEM image of the composite hydrogen-sensitive material prepared in Example 4 of the present invention;
[0038] Figure 5 is a TEM image of the composite hydrogen-sensitive material prepared in Example 33 of the present invention;
[0039] Figure 6 is a TEM image of the composite hydrogen-sensitive material prepared in Example 34 of the present invention;
[0040] Figure 7 is a curve diagram showing the change in resistance of the composite hydrogen-sensitive material prepared in Example 1 of the present invention at room temperature (298K) over time;
[0041] Figure 8 This is a curve chart showing the change in resistance of the composite hydrogen-sensitive material prepared in Example 33 of the present invention at room temperature (298K) over time. DETAILED DESCRIPTION
[0042] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] The present invention provides a composite hydrogen-sensitive material. The composite hydrogen-sensitive material comprises a porous material ZIF-8 and palladium nanoparticles loaded on the porous material ZIF-8.
[0045] The porous material ZIF-8 can not only filter out interfering gases that affect hydrogen response, but also accelerate the response speed of hydrogen due to its high specific surface area pre-adsorbing effect on hydrogen; the present invention combines palladium nanoparticles and porous material ZIF-8, and the Pd atoms will produce a synergistic effect with the zinc atoms in the porous material ZIF-8, so that the obtained composite hydrogen-sensitive material can quickly, highly sensitively and highly selectively detect the hydrogen concentration in the environment under room temperature conditions. Compared with hydrogen-sensitive materials such as metal oxides, the composite hydrogen-sensitive material does not require heating, has low power consumption, good selectivity and fast response speed.
[0046] The composite hydrogen-sensitive material provided by the present invention is directly aimed at the leakage monitoring and safety issues of hydrogen, a new generation of clean energy. It can quickly detect and respond to hydrogen leakage in the environment at room temperature to ensure its safe use. It can be used in hydrogen production, hydrogenation, hydrogen storage and other hydrogen use links.
[0047] In a preferred embodiment, palladium nanoparticles are uniformly dispersed in the pores of the porous material ZIF-8. Metal palladium can reversibly react with H2 at room temperature to catalyze the dissociation of hydrogen into hydrogen atoms, but single palladium nanoparticles tend to agglomerate at room temperature, resulting in a slow hydrogen response time. The present invention avoids agglomeration of palladium nanoparticles by uniformly dispersing them in the pores of the porous material ZIF-8, thereby further improving the response speed.
[0048] In a preferred embodiment, the palladium nanoparticles have a particle size range of 10 to 20 nm and are uniform in size.
[0049] In a preferred embodiment, the morphology of the palladium nanoparticles includes one or more of a cube, an octahedron, a cuboctahedron and a sphere. Under the above morphology, the exposure ratio of the {111} crystal plane is relatively high, which can better carry out the hydrogen adsorption reaction. Therefore, by controlling the morphology and size of the palladium nanoparticles, the response speed and sensitivity to hydrogen are further improved.
[0050] In a preferred embodiment, the particle size of the composite hydrogen-sensitive material is in the range of 300 to 500 nm, and its morphology includes one or more of cube, rhombic dodecahedron and sheet, and more preferably rhombic dodecahedron.
[0051] The present invention also proposes a method for preparing a composite hydrogen-sensitive material, which comprises the following steps:
[0052] (1) mixing a palladium precursor, HCl and water, and mixing the obtained precursor solution with a surfactant and a reducing agent to react to obtain palladium nanoparticles;
[0053] (2) The palladium nanoparticles, 2-methylimidazole, a zinc source and a solvent are mixed and reacted.
[0054] In the method described in the present invention, Pd nanoparticles with controllable morphology can be prepared in an aqueous solution by a one-step synthesis method. Compared with the existing seed method (i.e., a two-step method) for preparing palladium nanoparticles, the one-step synthesis method does not require the pre-preparation of palladium nanoparticles as seeds, and the operation is simple; on the other hand, it does not require the introduction of necessary morphology control agents such as bromide ions or iodide ions with strong adsorption effects, and single-crystal palladium nanoparticles with different crystal faces can be obtained by simply adjusting the amount of HCl added.
[0055] Furthermore, the present invention utilizes an in-situ assembly method to composite palladium nanoparticles with the porous material ZIF-8, so that the palladium nanoparticles can be evenly dispersed in the pores of the porous material, thereby making the prepared composite hydrogen-sensitive material have better hydrogen sensing performance at room temperature; at the same time, by using hydrochloric acid (HCl) to prepare the precursor solution, the exposure ratio of the {111} crystal plane of the prepared palladium nanoparticles is high, thereby further improving the hydrogen sensing performance of the composite hydrogen-sensitive material.
[0056] In the method described in the present invention, palladium nanoparticles with high exposed {111} crystal faces are prepared, and the palladium nanoparticles are composited with the porous material ZIF-8, and the palladium nanoparticles with smaller sizes are more evenly dispersed in the pores of the porous material, so that the prepared composite hydrogen-sensitive material has a fast response speed to hydrogen and high sensitivity at room temperature, good mechanical strength, wet heat stability and chemical stability, and can quickly detect and respond to hydrogen leakage in the environment to ensure its safe use; at the same time, the preparation method is simple to operate, has good stability, low raw material price, and is easy to be mass-produced and applied.
[0057] In a preferred embodiment, in step (1), in the precursor solution, the molar ratio of the palladium precursor to HCl is 1:1-5, and Pd nanoparticles with different morphologies can be obtained by adjusting the amount of HCl.
[0058] Further preferably, in step (1), the concentration of the palladium precursor in the precursor solution is 0.001 to 0.02 mol / L (abbreviated as M).
[0059] In a preferred embodiment, in step (1), the palladium precursor is selected from one or more of palladium acetylacetonate, palladium chloride (PdCl2), palladium nitrate and palladium sulfate.
[0060] In a preferred embodiment, in step (1), the surfactant is selected from one or more of cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), polyvinylpyrrolidone (PVP), cetylpyridinium chloride (CPC) and sodium dodecylbenzene sulfonate (SDBS), preferably CPC.
[0061] In a preferred embodiment, in step (1), the reducing agent is selected from one or more of ascorbic acid, sodium borohydride and sodium hypophosphite, preferably ascorbic acid.
[0062] In a preferred embodiment, in step (1), the molar ratio of the palladium precursor, the surfactant and the reducing agent is 1:4-20:0.4-2.
[0063] In a preferred embodiment, in step (1), the reaction temperature is 50-100° C. and the reaction time is 1-13 h.
[0064] Further preferably, in step (1), the step of mixing and reacting the obtained precursor solution with a surfactant and a reducing agent to obtain palladium nanoparticles comprises:
[0065] The obtained precursor solution is mixed with a surfactant at 50 to 100° C., and then a reducing agent is added and reacted for 5 to 15 minutes, and then reacted at 50 to 100° C. for 1 to 12 hours;
[0066] The obtained reaction product is washed and dried at 40 to 100° C. for 12 to 36 hours to obtain palladium nanoparticles.
[0067] More preferably, the obtained precursor solution is mixed and stirred at 70-90° C., a reducing agent is added and reacted for 5-15 min, and then the temperature is changed to 60-100° C. and reacted for 2-12 h.
[0068] In a preferred embodiment, the molar ratio of the palladium precursor to 2-methylimidazole is 1:10-60.
[0069] In a preferred embodiment, in step (2), the molar ratio of the 2-methylimidazole to the zinc source is 1 to 4:1.
[0070] In a preferred embodiment, in step (2), the reaction temperature is 0-50°C, specifically, for example, 0°C, 10°C, 20°C, 30°C, 40°C or 50°C; the reaction time is 1-8h, specifically, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0071] In a preferred embodiment, in step (2), the zinc source is selected from one or more of zinc nitrate hexahydrate, zinc chloride and zinc sulfate.
[0072] In a preferred embodiment, in step (2), the solvent is selected from one or more of methanol, N,N-dimethylformamide, ethanol, water and n-heptane.
[0073] In a specific embodiment, step (2) comprises:
[0074] Step A1, mixing 2-methylimidazole, a zinc source and a solvent and stirring to obtain a mixed solution;
[0075] Step A2: mixing the palladium nanoparticles with the mixed solution, and then stirring to react, followed by washing, centrifugation and drying.
[0076] The present invention does not limit the specific drying method in step A2, and drying can be performed by evaporation at room temperature or in a drying device. Preferably, the drying temperature is 40 to 100° C. and the drying time is 12 to 36 hours.
[0077] In a specific embodiment, step A1 comprises: mixing and stirring 2-methylimidazole, a zinc source, a solvent and a surfactant to obtain a mixed solution, so that composite hydrogen-sensitive materials with different morphologies can be prepared. Wherein, the surfactant is hexadecyltrimethylammonium chloride (CTAC) or hexadecyltrimethylammonium bromide (CTAB).
[0078] The present invention also proposes a composite hydrogen-sensitive material prepared by the method as described above.
[0079] The composite hydrogen-sensitive material of the present invention has a stable structure, good selectivity, thermal stability and chemical stability, and can quickly detect and respond to hydrogen leakage in the environment to ensure its safe use; at the same time, the process for preparing the composite hydrogen-sensitive material is simple and environmentally friendly, the synthetic raw materials are inexpensive, and it is easy to mass-produce and apply.
[0080] The present invention also provides a hydrogen sensor, wherein the raw materials for preparing the hydrogen sensor include the composite hydrogen-sensitive material as described above.
[0081] The present invention also proposes an application of the composite hydrogen-sensitive material as described above in hydrogen detection.
[0082] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0083] Example 1
[0084] This example is used to illustrate the composite hydrogen-sensitive material and its preparation method described in the present invention.
[0085] (1) diluting 37% hydrochloric acid (HCl) with deionized water, and then mixing with PdCl2 powder to obtain a precursor solution, wherein the concentration of PdCl2 is 0.01M and the concentration of HCl is 0.02M;
[0086] (2) Pour 10 mL of a 0.02 M CPC surfactant solution into a 50 mL glass bottle, add 4 mL of the precursor solution and mix well, place the glass bottle containing the mixed solution in a water bath at 80° C. and stir, add 1 mL of freshly prepared 0.02 M ascorbic acid dropwise after the solution is clarified, continue stirring for 2 minutes and then stand for 10 minutes, then heat to 90° C. and react for 6 hours, then cool the reaction product and wash it with deionized water and ethanol for several times, and dry it at 60° C. for 24 hours to obtain palladium nanoparticles, that is, the molar ratio of the amounts of PdCl2, CPC and ascorbic acid is 1:5:0.5;
[0087] (3) 0.0493 g (i.e., 0.0006 mol) of 2-methylimidazole, 0.089 g of Zn(NO3)2·6H2O (i.e., 0.0003 mol) and methanol were mixed and stirred, and the volume was fixed to 50 mL to obtain a mixed solution;
[0088] (4) Mixing the palladium nanoparticles prepared in step (2) with the mixed solution prepared in step (3) (i.e., the molar ratio of the palladium precursor to 2-methylimidazole is 1:15), stirring the reaction at 0°C (ice water bath) for 4 hours, washing twice with methanol, and then collecting the product by centrifugation, and then vacuum drying at 60°C for 24 hours to obtain a composite hydrogen-sensitive material.
[0089] Example 2
[0090] The method of Example 1 is used for implementation, except that in step (1), in the precursor solution, the concentration of PdCl2 is 0.0025M, and the concentration of HCl is 0.005M, that is, the molar ratio of the PdCl2, CPC and ascorbic acid is 1:20:2, and the molar ratio of the palladium precursor and 2-methylimidazole is 1:60.
[0091] Example 3
[0092] The method described in Example 1 is used for implementation, except that in step (1), in the precursor solution, the concentration of PdCl2 is 0.0075M, and the concentration of HCl is 0.015M, that is, the molar ratio of the amounts of PdCl2, CPC and ascorbic acid is 3:20:2, and the molar ratio of the amounts of the palladium precursor and 2-methylimidazole is 1:20.
[0093] Example 4
[0094] The method described in Example 1 is used for implementation, except that in step (1), in the precursor solution, the concentration of PdCl2 is 0.005M, and the concentration of HCl is 0.01M, that is, the molar ratio of the amounts of PdCl2, CPC and ascorbic acid is 1:10:1, and the molar ratio of the amounts of the palladium precursor and 2-methylimidazole is 1:30.
[0095] Example 5
[0096] The method described in Example 1 is followed, except that in step (2), the CPC surfactant solution is replaced with a CTAB surfactant solution.
[0097] Example 6
[0098] The method described in Example 1 is followed, except that in step (2), the CPC surfactant solution is replaced by a CTAC surfactant solution.
[0099] Example 7
[0100] The method described in Example 1 is followed, except that in step (2), the CPC surfactant solution is replaced with a PVP surfactant solution.
[0101] Example 8
[0102] The method described in Example 1 is followed, except that in step (2), the CPC surfactant solution is replaced by a SDBS surfactant solution.
[0103] Example 9
[0104] The method described in Example 1 is followed, except that in step (2), the reducing agent ascorbic acid is replaced by sodium borohydride.
[0105] Example 10
[0106] The method described in Example 1 is followed, except that in step (2), the reducing agent ascorbic acid is replaced with sodium hypophosphite.
[0107] Embodiment 11
[0108] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 hours was replaced by changing the temperature to 90°C for reaction for 2 hours.
[0109] Example 12
[0110] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 hours was replaced by changing the temperature to 90°C for reaction for 4 hours.
[0111] Embodiment 13
[0112] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 hours was replaced by changing the temperature to 90°C for reaction for 8 hours.
[0113] Embodiment 14
[0114] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 hours was replaced by changing the temperature to 90°C for reaction for 10 hours.
[0115] Embodiment 15
[0116] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 hours was replaced by changing the temperature to 90°C for reaction for 12 hours.
[0117] Example 16
[0118] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 h was replaced by changing the temperature to 60°C for reaction for 6 h.
[0119] Embodiment 17
[0120] The method described in Example 1 was followed, except that in step (2), changing the temperature to 90°C for reaction for 6 h was replaced by changing the temperature to 70°C for reaction for 6 h.
[0121] Embodiment 18
[0122] The method described in Example 1 was followed, except that in step (2), the temperature was changed to 90°C for reaction for 6 hours and then the temperature was kept at 80°C for 6 hours instead of being changed to 90°C for reaction for 6 hours.
[0123] Embodiment 19
[0124] The method described in Example 1 was followed, except that in step (2), the temperature was raised to 100° C. for 6 h instead of changing the temperature to 90° C. for 6 h.
[0125] Embodiment 20
[0126] The method described in Example 1 was followed, except that in step (2), drying at 60° C. for 24 h was replaced by drying at 40° C. for 24 h.
[0127] Embodiment 21
[0128] The method described in Example 1 was followed, except that in step (2), drying at 60° C. for 24 h was replaced by drying at 80° C. for 24 h.
[0129] Embodiment 22
[0130] The method described in Example 1 was followed, except that in step (2), drying at 60° C. for 24 h was replaced by drying at 100° C. for 24 h.
[0131] Embodiment 23
[0132] The method described in Example 1 was followed, except that in step (2), drying at 60° C. for 12 h was replaced by drying at 60° C. for 24 h.
[0133] Embodiment 24
[0134] The method described in Example 1 was followed, except that in step (2), drying at 60° C. for 36 hours was used instead of drying at 60° C. for 24 hours.
[0135] Embodiment 25
[0136] The method described in Example 1 was followed, except that in step (4), stirring the reaction at 0°C for 2 h was replaced by stirring the reaction at 0°C for 4 h.
[0137] Embodiment 26
[0138] The method described in Example 1 was followed, except that in step (4), stirring the reaction at 0°C for 4 h was replaced by stirring the reaction at 0°C for 6 h.
[0139] Embodiment 27
[0140] The method described in Example 1 was followed, except that in step (4), stirring the reaction at 0°C for 4 h was replaced by stirring the reaction at 0°C for 8 h.
[0141] Embodiment 28
[0142] The method described in Example 1 was followed, except that in step (4), stirring the reaction at 0°C for 4 h was replaced by stirring the reaction at 20°C for 4 h.
[0143] Embodiment 29
[0144] The method described in Example 1 was followed, except that in step (4), stirring the reaction at 0°C for 4 h was replaced by stirring the reaction at 40°C for 4 h.
[0145] Embodiment 30
[0146] The method described in Example 1 was followed, except that in step (4), stirring the reaction at 0°C for 4 h was replaced by stirring the reaction at 50°C for 4 h.
[0147] Embodiment 31
[0148] The method described in Example 1 is followed, except that in step (1), the palladium precursor PdCl2 is replaced with palladium acetylacetonate.
[0149] Embodiment 32
[0150] The method described in Example 1 is followed, except that in step (1), the palladium precursor PdCl2 is replaced with palladium sulfate.
[0151] Embodiment 33
[0152] The method described in Example 1 was followed, except that 0.25 g of hexadecyltrimethylammonium chloride (CTAC) was additionally added in step (3).
[0153] Embodiment 34
[0154] The method described in Example 1 was followed, except that 1.6 g of cetyltrimethylammonium bromide (CTAB) was additionally added in step (3).
[0155] Embodiment 35
[0156] The method described in Example 1 is used for implementation, except that the palladium nanoparticles are loaded on the porous ZIF-8 material by an impregnation method;
[0157] Specifically, the preparation method of the composite hydrogen-sensitive material includes:
[0158] (1) preparing palladium nanoparticles according to the method described in Example 1;
[0159] (2) 0.0493 g (i.e., 0.0006 mol) of 2-methylimidazole, 0.089 g of Zn(NO3)2·6H2O (i.e., 0.0003 mol) and a methanol solution were mixed and stirred, and the volume was fixed to 50 mL to obtain a mixed solution, which was stirred and reacted at 0°C for 4 h, washed twice with methanol, and then the product was collected by centrifugation, and then vacuum dried at 60°C for 24 h to obtain ZIF-8;
[0160] (3) The palladium nanoparticles prepared in step (1) and the ZIF-8 obtained in step (2) were dissolved in anhydrous ethanol and ultrasonicated for 60 minutes, and then the product was collected by centrifugation and then vacuum dried at 60° C. for 24 hours to obtain a composite hydrogen-sensitive material.
[0161] Embodiment 36
[0162] The method described in Example 1 is followed, except that in step (1), hydrochloric acid is replaced by sodium chloride.
[0163] Embodiment 37
[0164] The method described in Example 1 is followed, except that in step (1), hydrochloric acid is replaced by sodium acetate.
[0165] Comparative Example 1
[0166] The method described in Example 1 is followed, except that in step (2), no ascorbic acid is added.
[0167] Test Example 1
[0168] (1) The palladium nanoparticles prepared in Examples 1 and 4 were characterized using a transmission electron microscope (TEM). The results are as follows: Figure 1 , 3 shown.
[0169] Depend on Figure 1 It can be seen that the palladium nanoparticles prepared in Example 1 are spherical and uniform in size.
[0170] Depend on Figure 3 It can be seen that the palladium nanoparticles prepared in Example 4 have spherical, cubic and other morphologies.
[0171] (2) The composite hydrogen-sensitive materials prepared in Example 1, Example 4, and Examples 33-34 were characterized by TEM. The results are as follows: Figure 2 / 4 / 5 / 6.
[0172] Depend on Figure 2 It can be seen that the composite hydrogen-sensitive material prepared in Example 1 is a rhombic dodecahedron, and the palladium nanoparticles are uniformly dispersed in ZIF-8.
[0173] Depend on Figure 4 It can be seen that the composite hydrogen-sensitive material prepared in Example 4 is a rhombic dodecahedron, and the palladium nanoparticles are relatively evenly dispersed in the ZIF-8.
[0174] Depend on Figure 5 It can be seen that the composite hydrogen-sensitive material prepared in Example 33 is a cube, and palladium nanoparticles are dispersed in ZIF-8.
[0175] Depend on Figure 6 It can be seen that the composite hydrogen-sensitive material prepared in Example 34 is a flaky structure, and the palladium nanoparticles are uniformly dispersed in ZIF-8.
[0176] Test Example 2
[0177] In this test example, when testing the hydrogen sensing performance of the hydrogen sensitive material, the hydrogen sensitive material is placed in a sealed cavity, and a dry hydrogen and air mixture is introduced, wherein the concentration of hydrogen is 0.02-2%. All tests are measured at room temperature (-25°C).
[0178] (1) The composite hydrogen-sensitive materials prepared in Example 1 and Example 33 were subjected to the following test: a certain mass of sample was placed in an agate mortar, pine alcohol was added, and the sample was fully ground into a slurry, which was evenly coated on a ceramic tube to prepare a component. After drying at room temperature for 24 hours, the sample was aged on a gas-sensitive aging table at 80 mA for 72 hours and at 140 mA for 2 hours to obtain a hydrogen sensor. The aged sensor element was inserted into the Elite gas-sensitive test system (CGS-8) to test its resistance change. The results were as follows: Figure 7-8 shown.
[0179] Depend on Figure 7 It can be seen that the response time of Example 1 is 13 s.
[0180] Depend on Figure 8 It can be seen that the response time of Example 33 is 23s.
[0181] (2) The composite hydrogen-sensitive materials prepared in Examples 1-37 and Comparative Example 1, and the palladium nanoparticles prepared in Example 1 were used as hydrogen-sensitive materials and tested in an Elite gas-sensitive test system (CGS-8). The hydrogen-sensitive materials were placed in a sealed 500 ml chamber, and a hydrogen-air mixed gas (hydrogen 1%) was introduced to diffuse freely throughout the sealed chamber. The resistance-time curve was measured at room temperature (298 K) to calculate the response time (t 90 ), and calculated the average value of 5 measurements. The test results are shown in Table 1.
[0182] Table 1
[0183]
[0184]
[0185]
[0186] It can be seen from Table 1 that the composite hydrogen-sensitive materials prepared in Examples 1-37 of the present invention have a fast response speed, and the composite hydrogen-sensitive materials in Examples 1-34 have an even faster response speed, indicating that the preparation method provided by the present invention improves the performance of the composite hydrogen-sensitive materials through the design of raw materials and steps.
[0187] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite hydrogen-sensitive material, characterized in that: The composite hydrogen-sensitive material comprises a porous material ZIF-8 and palladium nanoparticles loaded on the porous material ZIF-8.
2. The composite hydrogen-sensitive material according to claim 1, characterized in that: In the composite hydrogen-sensitive material, the particle size of the palladium nanoparticles ranges from 10 to 20 nm, and the morphology thereof includes one or more of a cube, an octahedron, a cuboctahedron and a sphere; Preferably, the palladium nanoparticles are loaded in the pores of the porous material ZIF-8.
3. The composite hydrogen-sensitive material according to claim 1, characterized in that: The particle size of the composite hydrogen-sensitive material is in the range of 300-500 nm, and its morphology includes one or more of a cube, a rhombic dodecahedron and a sheet.
4. A method for preparing a composite hydrogen-sensitive material, characterized in that: The method comprises the following steps: (1) mixing a palladium precursor, HCl and water, and mixing the obtained precursor solution with a surfactant and a reducing agent to react to obtain palladium nanoparticles; (2) The palladium nanoparticles, 2-methylimidazole, a zinc source and a solvent are mixed and reacted.
5. The method according to claim 4, characterized in that In step (1), the molar ratio of the palladium precursor to HCl in the precursor solution is 1:1-5.
6. The method according to claim 4 or 5, characterized in that: In the precursor solution, the concentration of the palladium precursor is 0.001-0.02 mol / L.
7. The method according to claim 4, characterized in that In step (1), the palladium precursor is selected from one or more of palladium acetylacetonate, palladium chloride, palladium nitrate and palladium sulfate; Preferably, in step (1), the surfactant is selected from one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, polyvinylpyrrolidone, cetylpyridinium chloride and sodium dodecylbenzenesulfonate; Preferably, in step (1), the reducing agent is selected from one or more of ascorbic acid, sodium borohydride and sodium hypophosphite; Preferably, in step (1), the molar ratio of the palladium precursor, the surfactant and the reducing agent is 1:4-20:0.4-2; Preferably, in step (1), the reaction temperature is 50-100° C. and the reaction time is 1-13 h.
8. The method according to claim 4, characterized in that In step (1), the obtained precursor solution is mixed with a surfactant and a reducing agent and reacted to obtain palladium nanoparticles, which comprises: The obtained precursor solution is mixed with a surfactant at 50 to 100° C., and then a reducing agent is added and reacted for 5 to 15 minutes, and then reacted at 50 to 100° C. for 1 to 12 hours; The obtained reaction product is washed and dried at 40 to 100° C. for 12 to 36 hours to obtain palladium nanoparticles.
9. The method according to claim 4, characterized in that The molar ratio of the palladium precursor to 2-methylimidazole is 1:10-60; Preferably, in step (2), the molar ratio of the 2-methylimidazole to the zinc source is 1 to 4:
1.
10. The method according to claim 4 or 9, characterized in that: In step (2), the reaction temperature is 0 to 50° C. and the reaction time is 1 to 8 hours.
11. The method according to claim 4 or 9, characterized in that: In step (2), the zinc source is selected from one or more of zinc nitrate hexahydrate, zinc chloride and zinc sulfate; Preferably, in step (2), the solvent is selected from one or more of methanol, N,N-dimethylformamide, ethanol, water and n-heptane.
12. The method according to claim 4, characterized in that Step (2) comprises: A1, 2-methylimidazole, a zinc source and a solvent are mixed and stirred to obtain a mixed solution; A2. Mixing the palladium nanoparticles with the mixed solution, stirring for reaction, and then washing, centrifuging and drying.
13. A composite hydrogen-sensitive material prepared by the method according to any one of claims 4 to 12.
14. A hydrogen sensor, characterized in that: The raw material for preparing the hydrogen sensor includes the composite hydrogen-sensitive material according to any one of claims 1-3 and 13.
15. Use of the composite hydrogen-sensitive material according to any one of claims 1 to 3 and 13 in hydrogen detection.